Shifts of Phrasal Verb in Quinn’s Dancing at Midnight - Devi Hellystia (Universitas Syiah Kuala, 2019)
This research tries to investigate shift of phrasal verb in the novel Dancing at Midnight that written by Julia Quinn. The purposes of this research are: 1)to find out the shift that occurred in the novel Dancing at Midnight and its Indonesian translation Dansa Tengah Malam, 2) to describe the causes of shift that occurred in the novel. The method that is used in this research is descriptive qualitative. The result shows two types of shift they are level and category shift which category shift divided into a structure, unit, class, and intrasystem shift. Level shifts that were found are 78 data or 55,8% out of 140 data. Structure shift 27 data or 19,3% , unit shift 23 data or 16,4%, class shift 9 data or 6,4% and intrasystem shift 3 data or 2,1%. there are structure and semantic adjustments in the translation p